Features of e-mail discourse in an Iranian organization - Madanchian, Mitra (2012)
This study investigates features of email discourse in workplace communication. Email exchanges are analyzed in order to clarify how members of an organization interact with each other using emails to achieve specific communicative needs of the organization. Therefore, this study assumes that email discourse is a social action, which is utilized by the employees within the organization and it is part of social practice. There is a gap in understanding or knowledge about how emails are used in Iranian organization within the business context. Therefore, a study of Iranian business emails may provide insights into Iranian ways of communication via emails. The data of this study consist of a corpus of email messages (N=112) which are exchanged among members of a selected Iranian organization and collected over a stipulated period. The present study used both quantitative and qualitative methods of analysis with an emphasis on qualitative analysis. The present study drew on the Speech Act theory and Conversational Structure framework as the basis for analyzing and explaining the qualitative data. In addition, data was analysed by using the Nvivo 8 software. A questionnaire was distributed to the employees of the selected organizations to solicit information on three important variables (email use, Attitude to email and email practice) and to determine the Iranian email practice in their workplace by using SPSS software. The study concludes that the employees in this Iranian organization adopted a variety of discourse and rhetorical strategies to achieve the specific communicative needs at the workplace. The selected strategies reflect the writer’s interpersonal relationship with their email intractants. Finally, the findings clarified the features of email discourse in the selected Iranian organization by drawing on the theories adopted in this study.